Local stability analysis of a predator-prey interaction model with harvesting - Pañares, Trisha Ann J. (College of Science, University of the Philippines Cebu, 2022)
Community ecology has long studied local stability. Stability indicates whether a disrupted ecological system returns to its original stable state. In unstable populations, even little disturbances can cause species extinction. That is why ecologists have been striving to develop strategies to stabilize natural ecosystems and sustain the staggering biodiversity observed. Predator-prey models are of particular interest to mathematicians and ecologists because they address environmental issues such as community morbidity and how to control it, optimal harvest policy for community sustainability, and others. In this study, we analyze a simple ratio-dependent predator-prey model where the predator population is harvested. The system's equilibrium points are studied, and their local stability is assessed. Furthermore, a numerical simulation of the examined model is carried out to support the theoretical observations.The study's findings may aid in the development of control strategies for harvested predator-prey systems.